Labor Market Effects of Migration-Related Supply Shocks: Evidence from Internal Refugees in Colombia (2009)
We exploit the exogenous nature of forced migrations in Colombia to understand how migrations from directly affected areas influence labour markets not directly touched by conflict. Using an instrumental variables strategy, we estimate the causal impact of these migrations on the urban labour market. Our estimates suggest that these migrations substantially reduce wages for urban unskilled workers who compete for jobs with forced migrants. Given the widespread problem of civilian displacement during civil wars in the developing world, and the robust relationship between poverty and civil wars, our results have broad implications for economic development.